Emotional Support from AI Chatbots: Should a Supportive Partner Self-Disclose or Not? - Meng, Jingbo; Dai, Yue (Nancy) (Journal of computer-mediated communication, 2021)
Abstract This study examined how and when a chatbot’s emotional support was effective in reducing people’s stress and worry. It compared emotional support from chatbot versus human partners in terms of its process and conditional effects on stress/worry reduction. In an online experiment, participants discussed a personal stressor with a chatbot or a human partner who provided none, or either one or both of emotional support and reciprocal self-disclosure. The results showed that emotional support from a conversational partner was mediated through perceived supportiveness of the partner to reduce stress and worry among participants, and the link from emotional support to perceived supportiveness was stronger for a human than for a chatbot. A conversational partner’s reciprocal self-disclosure enhanced the positive effect of emotional support on worry reduction. However, when emotional support was absent, a solely self-disclosing chatbot reduced even less stress than a chatbot not providing any response to participants’ stress. Lay Summary In recent years, AI chatbots have increasingly been used to provide empathy and support to people who are experiencing stressful times. This study compared emotional support from a chatbot compared to that of a human who provided support. We were interested in examining which approach could best effectively reduce people’s worry and stress. When either a person or a chatbot was able to engage with a stressed individual and tell that individual about their own experiences, they were able to build rapport. We found that this type of reciprocal self-disclosure was effective in calming the worry of the individual. Interestingly, if a chatbot only reciprocally self-disclosed but offered no emotional support, the outcome was worse than if the chatbot did not respond to people at all. This work will help in the development of supportive chatbots by providing insights into when and what they should self-disclose.